Utilization of infrared heating innovation in a 25 Kg Capacity Satay Grilling Machine for MSMEs in Benowo District West Surabaya - Yustianto, Dwi; Riyadi, Slamet; Siswadi, Siswadi (Fakultas Teknik-Universitas Wijaya Putra, 2023)
Sate is a favorite food in Indonesia. Various types of satay ingredients are used by traders, starting with chicken, goat, and beef. The process of grilling satay requires special treatment to get a delicious taste. We conducted outreach and made satay burners with a capacity of 25 kg to increase capacity. We came up with this idea because we identified that most satay operators face difficulties in burning during the process. This counseling was carried out for Sate MSMEs at the Sememi Culinary Tourism Center, West Surabaya. This machine is equipped with new technology features that no longer use charcoal for the satay burning process. However, it uses an HD-262 infrared heater, which is fueled by LPG gas. This infrared heater can have its temperature controlled via digital control, which is connected to several other infrared components. The temperature produced by this infrared heater is optimal for food that is served through grilling.